Perbandingan Asupan Vitamin A, Ca, dan Zn Antara Anak Stunting Dan Tidak Stunting Di Cirebon - Siti Pandanwangi TW; Akrom; Nurkhasanah; Ahmad Azrul Zuniarto (Postgraduate, University of Mataram, 2024)
The food consumed by children greatly affects how they will live in the future. The amount of nutrition that enters a child's body affects their health and intelligence. Vitamin A and minerals Ca, Zn are vital components in the body for the process of growth and development, endurance, and other important functions. The purpose of this study was to see the intake of vitamins A, Ca, and Zn between stunted and non-stunted children. The research method is observational with a cross sectional design. The population is toddlers who live in Tegalwangi, Cirebon Regency. Sample with age 24-60 month that parents are willing to fill out the consent form as research subjects. The time for the study began in January-May 2023. Data was collected using the 3x24 hour nutritional recall questionnaire method, followed by converting nutritional intake through the Nutrisurvey software. The results of the study for the stunting group obtained an average intake of vitamin A 285.3RE ± 242.34RE, Ca 233.12mg±180.7mg and Zn 2.95mg ± 0.97mg. Meanwhile, for the non-stunted group, the average intake of vitamin A was 591.0RE±735.5RE, Ca 604.5mg±906.7mg and Zn 5.3mg±3.8mg. Analysis of the difference between the intake of the two groups resulted in a P -value of 0.009 for vitamin A intake, a P -value of 0.007 for Ca, a p-value of 0.000 for Zn. There is a significant difference between stunted and non-stunted children.